2021
DOI: 10.18632/aging.203519
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific differences in DNA double-strand break repair of cycling human lymphocytes during aging

Abstract: The gender gap in life expectancy and cancer incidence suggests differences in the aging process between the sexes. Genomic instability has been recognized as a key factor in aging, but little is known about sex-specific differences. Therefore, we analyzed DNA double-strand break (DSB) repair in cycling human peripheral blood lymphocytes (PBL) from male and female donors of different age. Reporter-based DSB repair analyses revealed differential regulation of pathway usage in PBL from male and female donors wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 75 publications
2
12
0
Order By: Relevance
“…An accompanying analysis of survival data from 3.7 million cases in the SEER database, representing approximately 28% of the cancer population, confirmed that mortality rates are higher for males compared to females [2]. These clinically important sex differences are concordant with described sex differences in cell biology including, response to genotoxic stress [3,4], DNA repair [5,6], mutational burden [7,8], metabolism [9,10], and cell cycle regulation [11][12][13], as well as in systems biology including: immunity [14], metabolism [15,16], tissue repair [17,18], and longevity [19,20]. This suggests that therapies for all cancer patients may be advanced by a realistic translation of sex differences into clinical practice.…”
Section: Introductionmentioning
confidence: 64%
“…An accompanying analysis of survival data from 3.7 million cases in the SEER database, representing approximately 28% of the cancer population, confirmed that mortality rates are higher for males compared to females [2]. These clinically important sex differences are concordant with described sex differences in cell biology including, response to genotoxic stress [3,4], DNA repair [5,6], mutational burden [7,8], metabolism [9,10], and cell cycle regulation [11][12][13], as well as in systems biology including: immunity [14], metabolism [15,16], tissue repair [17,18], and longevity [19,20]. This suggests that therapies for all cancer patients may be advanced by a realistic translation of sex differences into clinical practice.…”
Section: Introductionmentioning
confidence: 64%
“…Recently, sex differences in biological aging and cellular senescence have drawn interest (Ng and Hazrati 2022). Despite evidence suggesting that estrogen inhibits senescence regulatory proteins, a lower capacity for DNA damage repair during aging was found in females than in males (Rall-Scharpf et al 2021). Following UV irradiation, female cells preferentially undergo cellular senescence, while male cells undergo apoptosis (Malorni et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Obviously, females and <35-year-old population showed fewer mutations in either allele site in rs7181866 or rs8031031 (Tables 2 and 3). This might be due to findings that DNA repair capacity decreased with age (Rall-Scharpf et al, 2021), and sex-specific differences in DNA repair have demonstrated that females appear to have smaller mutation loads than males (Fischer and Riddle, 2018). However, as age increases, the probability of cumulative mutations increases greatly, which means that the antioxidant capacity is reduced and leads to the risk of tumorigenesis induced by gradually increasing DNA damage.…”
Section: Discussionmentioning
confidence: 99%